Application of an aquatic plant ecosystem for swine wastewater polishment: a full-scale study. Issue 45 (25th September 2016) - Chien, C.C.; Yang, Z.H.; Cao, W.Z.; Tu, Y.T.; Kao, C.M.
Abstract: In Taiwan, swine wastewater has become one of the major causes of the deterioration of surface water quality. The objective of this study was to evaluate the efficacy of using aquatic plant ecosystem to polish the treated swine wastewater. In this study, a hog farm was selected as the case study site. The daily wastewater of the studied farm was approximately 40 m 3 /d. Eichhornia crassipes was used as the aquatic plant for water polishment in the aquatic plant basin. Influent and effluent samples from each treatment unit were collected for water quality analyses. Results show that although the conventional three-stage system (solid separation followed by anaerobic and aerobic treatment) was effective to remove more than 97% of suspended solid (SS), ammonia nitrogen (NH3 -N), chemical oxygen demand (COD), and biochemical oxygen demand (BOD), BOD and COD in effluents still could not meet the discharge standards. The full-scale study shows that the aquatic plant ecosystem played an important role in the swine wastewater polishment and more than 27% of SS, NH3 -N, COD, and BOD, could be removed further from the effluents of the three-stage system, and the treated water could comply with the discharge standards and also meet the water reuse standards for irrigation and road washing. Results of polymerase chain reaction (PCR), denaturing gradient gel electrophoresis (DGGE), and nucleotide sequence analyses indicate that a variation in microbial diversity in the treatment system was observed. The system contained significant amounts of microbial ribospecies, which contributed to the carbon and nitrogen removal. DGGE results show that disappearance of E. coli was observed indicating that the system could remove E. coli and pathogens effectively. Results indicate that the aquatic plant ecosystem can be combined with the conventional three-stage treatment system to further polish the swine wastewater effluent.